Dedicator of cytokinesis 8 (DOCK8) mutation impairs the differentiation of helper T cells by regulating the glycolytic pathway of CD4+ T cells - Panpan Jiang; Siyu Zhao; Xiaoyu Li; Shiyan Hu; Shuhan Chen; Yinming Liang; Lichen Zhang; Liaoxun Lu; Guofeng Fang; Lu Yang; Yanmei Huang; Heather Miller; et al. (MedComm, 2024)
Abstract Dedicator of cytokinesis 8 (DOCK8) deficiency is a primary immunodeficiency disease caused by mutations in exon 45 of the DOCK8 gene. The clinical signs primarily consist of increased serum IgE levels, eczema, repeated skin infections, allergies, and upper respiratory tract infections. Using CRISPR/Cas9 technology, we generated a DOCK8 exon 45 mutation in mice, mirroring the mutation found in patients. The results indicated that DOCK8 mutation impairs peripheral T cell homeostasis, disrupts regulatory T cells (Tregs) development, increases ICOS expression in Tregs within peripheral lymph nodes (pLn), and promotes Th17 cell differentiation within the spleen and pLn. Upon virus infection, DOCK8 mutation CD4+ T cells have a Th2 effector fate. RNA‐bulk sequencing data revealed alternations in the mTOR pathway of DOCK8 mutant CD4+ T cells. We observed that DOCK8 mutation upregulates the glycolysis levels in CD4+ T cells, which is related to the Akt/mTOR/S6/HIF‐1α pathway. In summary, our research elucidates that DOCK8 regulates the differentiation of helper T cells by modulating the glycolytic pathway in CD4+ T cells, thereby advancing the comprehension and offering potential treatment of diseases in DOCK8‐deficient patients.